Tax Basis for Transfer of Land Rights: Antinomy between Civil Law and State Administrative Law - Muchtar, Andhyka; Prihartono, Agus; Sri Agustina, Rani (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2025)
This study aims to understand the concept of taxation of transfer of land and building rights that is more legally certain. Understanding the concept of legal certainty requires seeing the Antinomy between the transaction value of the transfer of rights that has a civil law dimension and the transaction value based on the fair value of the land that has a State Administrative Law dimension. This study uses the doctrinal method or normative research, using the Statute Approach and the conceptual approach (conceptual Approch). The results of this study show that in order to ensure the legal certainty of taxation of transfer of land rights by understanding the theory of antinomy provides enlightenment that the land value for taxation should be determined based on the fair value of the land that can be accessed as public information. This concept will eliminate tax avoidance from taxpayers and avoid illegal levies from the Tax Office so that legal certainty can be created for the collection of taxation of transfer of land rights.